Pengaruh Komunikasi Dan Budaya Organisasi Terhadap Kinerja Pegawai Pada Kantor DPRD (Dewan Perwakilan Rakyat Daerah) Di Tangerang Selatan - Muhamad Pajar Ikhsanudin; Budhi Prabowo (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2026)
Abstract The purpose of this study was to determine the effect of communication and organizational culture on employee performance at the DPRD (Regional People's Representative Council) Office in South Tangerang. The method used was quantitative. The sampling technique used slovin samples, namely 73 respondents. Data analysis used validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, determination coefficients and hypothesis tests. The results of this study are communication influences employee performance with a determination coefficient value of 68.4% and the hypothesis test obtained t count> t table or (12.523> 1.666). Organizational culture has a significant effect on employee performance with a determination coefficient value of 58.8% and the hypothesis test obtained t count> t table or (10.191> 1.666). Communication and organizational culture have a significant effect on employee performance with a regression equation Y = 9.723 + 0.536X1 + 0.221X2. The determination coefficient value is 70.2% while the remaining 29.8% is influenced by other factors. The hypothesis test obtained a calculated F value > F table, or (85.793 > 2.38).